Pausing preceding and following that in that-clauses of Obama's G-20 Summit Speech in London: read vs. spontaneous speech - Yonca Ozkan,; Bilal Genc,; Erdoğan Bada, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2010)
Readers or speakers of a particular language break up sentences into lexical/syntactic entities while reading or speaking. Pausing, being one indispensible characteristic of this process, forms a basis for this study. President Obama‘s address at the G-20 summit was analyzed in terms of intrasentential pausing strategies with due focus on duration of pauses preceding and following the that complementizer in noun and adjective type that-clauses. Recordings of the speech were analyzed in two separate parts: (1) the first part - assumed as pre-prepared and thus considered as read speech, and the second – question/answer session –considered as spontaneous speech. Pauses were measured in milliseconds utilizing Goldwave™, the sound analyzing software, and later, a comparison was carried out between pauses in the two speech types to observe any potential differences and/or similarities. Overall findings obtained reveal that while preceding pauses in read speech were significantly longer than following ones, in spontaneous speech, however, the difference was statistically insignificant. One interesting outcome was found to be clause-type specific, in that while preceding pauses regarding adjective clauses were considerably longer than following pauses in read speech, with noun clauses, however, the difference was insignificant. And, in spontaneous speech, the situation was completely the opposite, such that while following pauses concerning noun-clauses were significantly longer, regarding adjectives, although preceding pauses were observed to be longer, the length did not display any statistically significant difference.